Stress and Strain State Analysis of Crack Front in Dissimilar Metal Welded Joints with Dual Field of Mechanical Heterogeneity and Residual Stress - Shun Zhang; He Xue; Yubiao Zhang; Kuan Zhao; Jiaqing Zhang (Science and Technology of Nuclear Installations)
The micro-mechanical state at the crack front is one of the key factors affecting the stress corrosion cracking (SCC) growth behavior. The mechanical heterogeneity and residual stress in the dissimilar metal welded joint (DMWJ) induce the micro-mechanical state at the crack front to become more complex. The sandwich model and dual-field model of the DMWJ with inner surface axial crack were established in this study. The stress and strain states at the crack front with different crack locations and lengths under the interaction of the mechanical property and the residual stress were investigated. The results show that a more accurate evaluation of stress and strain states can be obtained when using the dual-field model to describe the material mechanical property and residual stress of the DMWJ. The sandwich model overestimates the crack driving force including the stress and strain at the crack front. The tensile stress in the middle of shallow cracks is smaller than that at both ends, while the tensile stress in the middle of deep crack is larger than that at both ends. The variation trend of the tensile stress and normal strain at the crack apex is basically the same as that of the residual stress with the crack depth. However, there is almost no normal plastic strain in the initial stage of crack propagation due to the small residual stress in the initial stage.